2020
DOI: 10.1093/intimm/dxaa004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical importance of the expression of CD4+CD8+ T cells in renal cell carcinoma

Abstract: Objective CD4+CD8+ T cells are expressed in some cancer patients including those with renal cell carcinoma (RCC). However, no reports have mentioned the clinical importance of this expression. We evaluated the expression of CD4+CD8+ T cells in patients with various cancer types to clarify clinical characteristics and prognostic importance significantly correlating with these T cells. Methods Expression of CD4+CD8+ T cells was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“… 47 Some previous studies also show that CD4+ T cells are upregulated and are significantly correlated with OS in RCC. 48–50 These previous results were consistent with our findings as a higher abundance ratio of Treg cells was identified in patients with worse OS. Nakanishi et al showed that mast cells played an important role in tumor growth, progression, and malignant aggressiveness of RCC tissues, 51 which was consistent with our findings that the larger quantity of mast cells resting was associated with a better prognosis.…”
Section: Discussionsupporting
confidence: 93%
“… 47 Some previous studies also show that CD4+ T cells are upregulated and are significantly correlated with OS in RCC. 48–50 These previous results were consistent with our findings as a higher abundance ratio of Treg cells was identified in patients with worse OS. Nakanishi et al showed that mast cells played an important role in tumor growth, progression, and malignant aggressiveness of RCC tissues, 51 which was consistent with our findings that the larger quantity of mast cells resting was associated with a better prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Previous study revealed that CD4 + T cells could promote tumor cell proliferation in RCC [55]. Moreover, another study found that CD4 + T cells in RCC patients were associated with favorable prognosis [56]. Therefore, BIRC5 may also regulate tumor cell biological process, thus affecting the prognosis of chRCC via CD4 + T cells.…”
Section: Discussionmentioning
confidence: 97%
“…Depletion or decrease of peripheral and intratumoral CD4+ T cells is more prone to inactivate the anti-tumor response and lead to deterioration and progression of the disease. Actually, various previous studies have already elucidated and verified that CD4+/CD8+ ratio can serve as independent prognostic predictors in multiple cancers, including laryngeal squamous cell carcinoma, 45 renal cell cancer, 72 nasopharyngeal carcinoma, 46 gastric cancer, 73 cervical cancer, 74 etc. Similarly, our study also demonstrated that CD4+/CD8+ ratio is a reliable and accurate prognostic predictor for patients with advanced osteosarcoma.…”
Section: Figurementioning
confidence: 99%